Heterogeneous reduction of CO2 to CO under aqueous conditions using transition metal based molecular catalysts - Reddu, Vikas (Nanyang Technological University, 2022)
Molecular catalysts, especially transition metal complexes, represent an excellent class of materials for electrochemical carbon dioxide reduction. They have a well-defined structure and can perform with superior selectivity. Their structure-performance relationship can be explored and established via electrochemical, spectroelectrochemical, and computational methods. A molecular level control on their structure enables performance modulation by tuning their first and second coordination spheres. Furthermore, tethering them to solid and conductive supports for heterogeneous catalysis significantly enhances their activity, selectivity, and stability. Among several classes of ligands, porphyrins, phthalocyanines, cyclams, and polypyridines (bipyridine, terpyridine, etc.) are well studied. However, reports based on higher oligo-pyridines, for their application towards electrochemical carbon dioxide reduction under aqueous conditions are scarce. Herein, we report quinquepyridine and quaterpyridine based transition metal complexes, whose performances ranked well among recently reported state-of-the-art complexes. Their high activity and efficiency could be attributed to their immobilization on carbon supports and to the various effects exerted by their second coordination sphere. First, three quinquepyridine-based cobalt complexes were synthesized with different types of functional group (-N(CH3)2, -NO2, -H) substitutions, allowing us to manipulate the electronic field around the metal center due to their varying electron donating and withdrawing tendencies. These were heterogenized onto carbon black, enabling them to perform in near neutral aqueous conditions (pH = 6.8). At an optimized catalyst loading of ~100 μg cm−2, dimethylamine- and nitro-substituted complexes outperformed the unsubstituted complex, wherein, dimethylamine substituted complex attained nearly 100% faradaic efficiency towards CO formation at a low overpotential (η) of 0.59 V (-0.7 V vs. RHE) and achieved a current density (j) of ~4.3 mA cm−2. It maintained its robust performance towards the formation of CO over a wide range of overpotential while suppressing the competitive hydrogen evolution reaction (HER). This enhanced activity compared to the unsubstituted complex was attributed to the effects exerted by the functional groups at the molecular level. Second, a di-substituted quaterpyridine based cobalt complex was synthesized and non-covalently tethered to MWCNT substrate, forming a hybrid catalyst Co-qpyCOOH/CNT. It was evaluated for CO2RR in aqueous conditions, wherein, MWCNT enabled an efficient electron transfer and catalytic cobalt sites coupled with the substituted ligand catalyzed the conversion of CO2 to CO. At an optimal and uniform loading, as evident from its HAADF-STEM images and a low Tafel slope, it exhibited remarkable catalytic activity, near exclusive selectivity, and high stability towards formation of CO. At a mere cathodic potential of -0.65 V vs. RHE (η = 0.54 V), it achieved a high partial current density of -6.7 mA cm-2 and a F.E.CO = 100%. In addition, with 20 hours of stable operation, HER remained practically undetected. Its hybrid structure due to non-covalent immobilization on a conductive substrate imparted intrinsic activity and much needed stability in performance, whereas -COOH groups may stabilize the intermediates by acting as H-bond donors, promoting catalytic activity. Overall, this thesis highlights the performance of lesser-explored oligo-pyridine based molecular catalysts for an efficient and highly selective reduction of carbon dioxide at mild operating conditions. Tethering to a conductive solid substrate and tuning of second sphere of coordination played an important role in their performance to achieve desired reduction product with high selectivity and activity.